Beamforming algorithms for endocardial border detection. Issue 10 (26th June 2018) - Kulina, Robert; Seetharam, Karthik; Agarwal, Sunil; Wiley, Brandon M.; Narula, Jagat; Chaudhry, Farooq A.; Sengupta, Partho P.
Abstract : Background: Software‐based beamforming which utilizes delay and standard beamforming is a signal processing technique that temporarily stores data from each probe element to improve specular reflections to improve the image resolution. We compared a software algorithm which uses delay and standard beamforming with delay and sum beamforming in standard, hardware to evaluate endocardial borders and need for echo contrast. Methods: In this prospective study, eligible participants were ≥ 18 years of age referred clinically for transthoracic echocardiograms. A limited study consisting of three views (apical 4, apical 3, and apical 2 chamber) was performed with the software‐based beamforming and standard platform. Number and quality of segments visualized were evaluated using a 17‐segment model. Quality of segments was graded as 0 = not visualized, 1 = incompletely visualized, or 2 = completely visualized. Overall quality score for each study (0 = poor, 1 = adequate, 2 = good) was reported. The need for contrast was determined by ASE guidelines. Results: A total of 101 patients (mean age 61 ± 16 years, males 52%) were enrolled. Mean number of segments visualized in apical 4‐ (6.28 vs 5.65, P  < .001), apical 3‐ (6.27 vs 5.54, P  < .001), and apical 2‐chamber views (6.26 vs 5.72 P  < .001) was higher with the software vs standard platform. The average overall score for image quality was significantly better for the software platform vs standard (1.4 vs 0.9, P  =< .001). With the software platform, 23% were judged as requiring contrast as compared with 45% for the standard platform ( P  < .001). Conclusions: Delay and standard beamforming in software platform identified more segments with better image quality when compared to the standard high‐end platform, decreasing the need for contrast usage.